The Old Latin book of Esther: An English translation. (June 2019) - Bellmann, Simon; Portier-Young, Anathea
In recent decades, a lively debate on the Hebrew and Greek versions of Esther story has developed, focusing on their text-historical and theological relationship. The discussion is enriched further by taking into account the Old Latin Esther, fully edited some 10 years ago by Jean-Claude Haelewyck as part of the Beuron Vetus Latina series. The extant Latin text likely dates back to 330–50 CE and represents an older, now-lost Greek Vorlage . Its numerous peculiarities substantially widen our understanding of ancient Esther traditions. The English translation presented here aims to elicit a broader interest in the Old Latin Esther and to facilitate a fresh discussion of its significance.